2021
DOI: 10.1172/jci.insight.143289
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA DRAIR is downregulated in diabetic monocytes and modulates inflammatory phenotype via epigenetic mechanisms

Abstract: Long noncoding RNAs (lncRNAs) are increasingly implicated in the pathology of diabetic complications. Here we examined the role of lncRNAs in monocyte dysfunction and inflammation associated with human type 2 diabetes mellitus (T2D). RNA-seq analysis of CD14 + monocytes from patients with T2D versus healthy controls revealed downregulation of antiinflammatory and anti-proliferative genes along with several lncRNAs, including a novel divergent lncRNA DRAIR (Diabetes Regulated anti-inflammatory RNA) and its near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…Furthermore, DRAIR overexpression increased anti-inflammatory genes via inhibition of G9a recruitment and enrichment of repressive H3K9me2 at their promoters. These studies suggest that inhibition of DRAIR mediated epigenetic mechanisms via its downregulation and increased G9a could contribute to monocyte dysfunction and inflammation in diabetes (52).…”
Section: Lncrna Functions In Monocytes and Macrophagesmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, DRAIR overexpression increased anti-inflammatory genes via inhibition of G9a recruitment and enrichment of repressive H3K9me2 at their promoters. These studies suggest that inhibition of DRAIR mediated epigenetic mechanisms via its downregulation and increased G9a could contribute to monocyte dysfunction and inflammation in diabetes (52).…”
Section: Lncrna Functions In Monocytes and Macrophagesmentioning
confidence: 81%
“…Interestingly, evidence shows non-conserved lncRNAs harbor a significant number of SNPs associated with cardiometabolic traits than conserved lncRNAs, which can enhance our understanding of the roles of key SNPs and lncRNAs in driving disease pathogenesis (129). Moreover, lncRNAs expressed from syntenic gene loci often showed limited sequence conservation but had functional similarities in mice and humans (27,29,49,52). These studies demonstrate the importance of prioritizing not only conserved but also non-conserved lncRNAs for future studies.…”
Section: Summary and Perspectivesmentioning
confidence: 93%
“…However, the role of most lncRNAs in TNBC is unclear. Diabetes regulated anti-inflammatory lncRNA (DRAIR) has been characterized as a critical player in type 2 diabetes mellitus [ 14 ]. However, its role in other human diseases is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al performed microarray analysis to screen out differential expressed mRNAs and lncRNAs between T2D patients and healthy control (14). Marpadga et al revealed downregulation of anti-inflammatory cytokines and antiproliferative genes, along with several lncRNAs, may promote chronic inflammation in T2D with RNA sequencing (15). Whether lncRNAs are involved blood cells or if they can be used to distinguish type 1 and 2 diabetes has not been explored.…”
Section: Introductionmentioning
confidence: 99%